Perception of health risks of electromagnetic fields by MRI radiographers and airport security officers compared to the general Dutch working population: a cross sectional analysis - van Dongen Diana; Smid Tjabe; Timmermans Daniëlle RM (BMC, 2011)
Abstract Background The amount of exposure to electromagnetic fields (EMF) at work is mainly determined by an individual's occupation and may differ from exposure at home. It is, however, unknown how different occupational groups perceive possible adverse health effects of EMF. Methods Three occupational groups, the general Dutch working population (n = 567), airport security officers who work with metal detectors (n = 106), and MRI radiographers who work with MRI (n = 193), were compared on perceived risk of and positive and negative feelings towards EMF in general and of different EMF sources, and health concerns by using analyses of variances. Data were collected via an internet survey. Results Overall, MRI radiographers had a lower perceived risk, felt less negative, and more positive towards EMF and different sources of EMF than the general working population and the security officers. For security officers, feeling more positive about EMF was not significantly related to perceived risk of EMF in general or EMF of domestic sources. Feeling positive about a source did not generalize to a lower perceived risk, while negative feelings were stronger related to perceived risk. MRI radiographers had fewer health concerns regarding EMF than the other two groups, although they considered it more likely that EMF could cause physical complaints. Conclusions These data show that although differences in occupation appear to be reflected in different perceptions of EMF, the level of occupational exposure to EMF as such does not predict the perceived health risk of EMF.